Relationship between Community Participation and Education Management in Fika Local Government Area of Yobe State, Nigeria - Mohammed, Musa Yusuf; Hussaini, Muhammad (NIU Journal of Humanities, 2018)
The study was to establish the level of management of primary school in Fika Local government of Yobe state Nigeria and was to determine the relationship between community participation and management of primary education. The study was guided by descriptive correlation with quantitative approaches. The population used in this study was 303 respondents from teachers, head teachers and community member from the study area. The sample size was 282 drawn through simple random sampling for teachers and head teachers and purposive sampling for community members. This study used questionnaire instrument to collect data from the respondents.  A research question drawn and one null hypothesis was formulated to test the relationship between community participation and management of primary schools Fikal Local Government, Yobe state. The data gathered were corrected and encoded in computer and statistically treated using the statistical package for social sciences (spss). Peasonâ€™s linear correlation was used to establish the relationship between community participation and management of primary school in Fika Local Government Area, Yobe State Nigeria. Findings revealed that there was no relationship between community participation and management of primary school since the significance value is (0.360) was far greater then 0.05, which is the maximum level of significance. The study concludes that there was no significant relationship between community participation and education management in Fika Local government of Yobe state Nigeria. The study also recommends to the government to establish a proper model of deliberately involving the community in affairs of the school. The study recommends that policy formulation on matters on management of secondary schools should be all inclusive so that it can address the societal needs. Therefore, the Ministry of Education ought to formulate a structure that allows for community participation at policy formulation stage to its implementation and maintenance.